Tunning Surface Hydrophilicity of PVA Nanofiber Bone Scaffolds Via Amino Acid and Nanohydroxyapatite Incorporation: - Rohul Rizki Mubaroq Hartman; Yessie Widya Sari; Yusril Yusuf (Program Studi Fisika Universitas Negeri Jakarta, 2026)
Polyvinyl alcohol (PVA) is a biodegradable and biocompatible polymer with potential use in bone tissue engineering. However, its excessively high hydrophilicity led to poor cell adhesion, limiting its suitability as a bone scaffold. This study investigates the modification of PVA nanofibers through the incorporation of negatively charged amino acids (aspartic acid, glutamic acid) and nano-hydroxyapatite (nHA) to tailor surface hydrophilicity. Electrospun nanofiber composites of Asp/PVA/nHA and Glu/PVA/nHA were fabricated with varying nHA concentrations. Higher nHA content was found to decrease hydrophilicity, whereby Asp/PVA/nHA and Glu/PVA/nHA with nHA concentration of 3.5% were within the ideal range for optimal cell adhesion and proliferation characterized by contact angle between 40o – 70o. Samples containing Asp exhibited a lower hydrophilicity compared to their respective Glu-containing counterparts, which may correlated to the difference side chain of Asp and Glu structure. Statistically significant differences (p ≤0.05) suggest that nHA and amino acids effectively modulate surface characteristics, supporting the potential of fine-tuning PVA hydrophilicity via nHA and amino incorporation for improved performance in bone tissue engineering applications.